MANAJEMEN PEMBANGUNAN KOTA DALAM PENATAAN LUBANG BEKAS TAMBANG DI KELURAHAN LOA BUAH SAMARINDA - . Hariati (Jurnal Administrative Reform, 2018)
This paper aims to describe how the construction of the city in the city of Samarinda in the management of ex-mine holes in Samarinda's Loa Buah Village. This study uses descriptive qualitative research with an interactive data analysis model. Data collection is done through field observations and interviews with key informants. The results of the study showed that the arrangement of the cities that were trapped in the mine pit had not run optimally due to the impact of mining activities, land compensation and lack of socialization from the Samarinda City government.Keyword: city development management, urban planning, mine pit.